Theoretical and methodological support for the elaboration of situational diagnoses: human aging in scope (PerCursos, 2023)
This article presents some theoretical and methodological support for the performance of situational diagnoses in the context of human aging.  This is a study of a social and descriptive nature, contemplating a proposal of theoretical-methodological systematization of situational diagnosis, followed by reports of experiences related to situational diagnoses carried out in Brazil and Portugal.  The importance of evidence, such as public information and sociodemographic and health indicators, as well as the use of potential strategies for listening to social actors (older people, workers and managers), is evidenced. There is also relevance of diagnoses qualifying.
Keywords: aging; situational diagnosis; monitoring indicators; management